TRACK AND BALANCE HELIKOPTER 412EP PADA SAMPEL DATA 1 - Utami, Noviana; I. Efriana, Ade (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2025)
Track and balance on the helikopter as a maintenance effort needs to be done to combine the helikopter vibration speed. Where vibration is a vibration that repeats periodically in a certain time that is influenced by amplitude and frequency. The standard normal distribution for the track and balance data of the 412 EP helikopter in sample 1 shows results that meet 81.594 - 99.061% with a sample standard deviation in the range of 0.426 - 1.113. This shows a fairly high accuracy for track and balance data. The helikopter amplitude after track and balance shows good results, with vibration speeds in the range of 315 - 327 rpm for 6 conditions (Fpg100 to L / Down).